2018
DOI: 10.1002/clc.22894
|View full text |Cite
|
Sign up to set email alerts
|

Why names matter for women: MINOCA/INOCA (myocardial infarction/ischemia and no obstructive coronary artery disease)

Abstract: The syndromes of myocardial infarction/myocardial ischemia with No Obstructive Coronary Artery Disease (MINOCA/INOCA) are increasingly evident. A majority of these patients have coronary microvascular dysfunction. These patients have elevated risk for a cardiovascular event (including acute coronary syndrome, myocardial infarction, stroke, and repeated cardiovascular procedures) and appear to be at higher risk for development of heart failure with preserved ejection fraction. Terminology such as coronary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 89 publications
3
40
1
5
Order By: Relevance
“…The term MINOCA is not completely clear regarding underlying causes and prognosis and will most probably be revised for a better description and division of patients with ischemic-coronary and non-coronary disorders 140 .…”
Section: Discussionmentioning
confidence: 99%
“…The term MINOCA is not completely clear regarding underlying causes and prognosis and will most probably be revised for a better description and division of patients with ischemic-coronary and non-coronary disorders 140 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of risk factors, including DM, HC and CKD, has been associated with CMD and INOCA in both experimental [5,57,63] and clinical [2,41,42,44] studies. For example, we previously showed that CMD was already present in swine 2.5 months after the induction of DM and HC in the absence of coronary atherosclerosis [63].…”
Section: Coronary Microvascular Dysfunctionmentioning
confidence: 99%
“…Common comorbidities of cardiovascular disease, including diabetes mellitus (DM), hypercholesterolemia (HC) and chronic kidney disease (CKD), are well-known risk factors for the development of coronary artery disease of both large epicardial arteries and smaller coronary arteries [8,13,18,31]. While it is well established that obstructive coronary artery disease (CAD) is a major cause of myocardial ischemia [19], there is increasing evidence that coronary microvascular dysfunction (CMD) also contributes to myocardial ischemia, not only in the presence of obstructive CAD [1,14,36,55] but also in patients without obstructive CAD, a situation referred to as 'Ischemia and No Obstructive Coronary Artery disease' (INOCA) [2,8,36,44]. Clinical studies have shown that INOCA is present in approximately one-third of men and two-thirds of women undergoing angiography for suspected ischemic heart disease and that cardiovascular death or myocardial infarction occurred in 6.7% of the patients without any signs of CAD and in 12.8% of patients with non-obstructive CAD [32,53].…”
Section: Introductionmentioning
confidence: 99%
“…Other strategies may also play a role in patients with chronic pain and Takotsubo cardiomyopathy, e.g., antidepressants. Changes in lifestyle including weight loss, smoking cessation, a high-fiber diet, increased consumption of fruits and vegetables, and sport are also beneficial for the prognosis of MINOCA patients [63].…”
Section: Current Managementmentioning
confidence: 99%